2014
DOI: 10.1007/s10488-014-0588-7
|View full text |Cite
|
Sign up to set email alerts
|

Does Insurance Matter? Implementing Dialectical Behavior Therapy with Two Groups of Youth Engaged in Deliberate Self-harm

Abstract: This paper presents the outcomes of a Dialectical Behavior Treatment (DBT) program, implemented in intensive outpatient care with two groups of adolescents (n=55 and n=45), ages 12–18, who engaged in deliberate self-harm (DSH) but had different insurance/funding sources and risk backgrounds. This pre-post study examined variability in clinical functioning and treatment utilization between the two groups and investigated moderating risk factors. Findings support DBT’s effectiveness in improving clinical functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 68 publications
0
26
1
5
Order By: Relevance
“…Four studies utilized a non-control group preand post-test comparison design; two included extended post-treatment follow-up (Fleischhaker et al, 2011; James et al, 2014; Tørmoen et al, 2014; Woodberry & Popenoe, 2008) and two studies included a comparison group (Mehlum et al, 2014; Rathus & Miller, 2002). Mehlum et al (2014) was the only randomized control trial study utilizing a usual care as the control condition.…”
Section: Review Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four studies utilized a non-control group preand post-test comparison design; two included extended post-treatment follow-up (Fleischhaker et al, 2011; James et al, 2014; Tørmoen et al, 2014; Woodberry & Popenoe, 2008) and two studies included a comparison group (Mehlum et al, 2014; Rathus & Miller, 2002). Mehlum et al (2014) was the only randomized control trial study utilizing a usual care as the control condition.…”
Section: Review Methodsmentioning
confidence: 99%
“…In the Fleischhaker et al (2011) study, although the sample size was small ( N = 12) the results indicated significant improvement in the areas of suicidality, self-harm, emotional dysregulation, and depression both at the end of treatment and at one-year follow-up. The more recent studies by James et al (2014), Tørmoen et al (2014), and Mehlum et al (2014) also utilized Rathus and Miller’s shortened adolescent DBT program with similar positive outcomes in regards to reduced self-harm at post-treatment and at 1 year follow-up in the case of the Tørmoen study. Of note is that the James study included intensified services similar to the original Rathus and Miller (2002) study.…”
Section: Treatment Lengthmentioning
confidence: 99%
See 3 more Smart Citations